Life Evolving : Molecules, Mind and Meaning. - De Duve, Christian (Oxford University Press, 2002)
In just a half century, humanity has made an astounding leap in its understanding of life. Now, one of the giants of biological science, Christian de Duve, discusses what we've learned in this half century, ranging from the tiniest cells to the future of our species and of life itself. With wide-ranging erudition, de Duve takes us on a dazzling tour of the biological world, beginning with the invisible workings of the cell, the area in which he won his Nobel Prize. He describes how the first cells may have arisen and suggests that they may have been like the organisms that exist today near dee.